Upaya Penurunan Anemia pada Remaja Putri dengan Deteksi Dini dan Suplementasi Zat Besi pada Siswi Sekolah Menengah Kejuruan (SMK) - Umriaty, Umriaty; Arti, Tias Dwi (Jurnal Pengabdian Dharma Bakti, 2019)
Iron deficiency anemia is the most common type of Anemia in Indonesia . The iron needs of adolescent girls aged 13-29 years are much higher than boys of the same age. Women iron intake is not only used to support growth, but is also used to replace the iron that is lost through the blood when menstruation every month. Therefore women are at risk for anemia. Anemia in adolescents will have a long impact on himself and the baby who will be born later. This activity is an effort to reduce the incidence of anemia in adolescents. In addition to knowing hemoglobin levels, this activity was also given information about anemia in adolescents and the consumption of iron supplements. The results of examination of hemoglobin levels in 16 female students (11.2%) out of a total of 142 female students were detected as having anemia. The results of this activity also showed an increase in the average hemoglobin level for these students from 10, 9 gr / dl to 11.7 gr / dl. In addition, the results of the examination after the intervention also showed that 8 female students who had anemia at the beginning then within one month had normal Hemoglobin levels (> 12 gr / dl).Keyword: adolescent anemia, early detection, iron supplementation